Learning to be inflexible: Enhanced attentional biases in Parkinson's disease. (September 2016) - Fallon, Sean James; Hampshire, Adam; Barker, Roger A.; Owen, Adrian M.
Abstract: Impaired attentional flexibility is considered to be one of the core cognitive deficits in Parkinson's disease (PD). However, the mechanisms that underlie this impairment are contested. Progress in resolving this dispute has also been hindered by the fact that cognitive deficits in PD are heterogeneous; therefore, it is unclear whether attentional impairments are only present in a subgroup of patients. Here, we demonstrate that what differentiates PD patients from age-matched controls is an inability to shift attention away from previously relevant information (perseveration) and an inability to shift attention towards previously irrelevant information (learned irrelevance). In contrast, there was no evidence that PD patients, compared to controls, were impaired in being able to appropriately attend to, or ignore, novel information. Furthermore, when patients were stratified according to their level of executive impairment, the executively impaired group showed a selective deficit in set formation compared to the unimpaired group, a behavioural pattern reminiscent of cortical dopamine depletion. Cumulatively, these results suggest that cognitive inflexibility in PD relates to a specific form of attentional dysfunction, in which learned attentional biases cannot be overcome.